The Effect of Performance Allowances, Organizational Motivation and Organizational Culture on Employee Performance Improvement in the University of Muhammadiyah Tangerang - Afifah Puspita Dinda Pratama; Dudung Hadiwijaya; Ismail Marzuki; Muljadi Muljadi (Eduvest - Journal of Universal Studies, 2025)
The subjects of this research were all employees at the Tangerang Muhammadiyah University. The total population in this study was 523 people with a sample size of 83 people. The data collection method is through a survey using a questionnaire. The data analysis technique used in this research is multiple regression. Based on the results of data processing and analysis, it can be concluded that (1) performance allowance (X1) shows that there is a positive and significant influence on employee performance with the equation Y = 26,496 + 0.326X1 + 0.378X2-0.062X3 + e. The hypothesis test calculation t is 0.002 < 0.05 and the t value is 3.202 > t table 1.990. (2) organizational motivation (X2) shows that there is a positive and significant influence on employee performance with a hypothesis test calculation of t of 0.000 < 0.05 and a t value of 3.848 > t table 1.990. (3) organizational culture (X3) shows that there is no influence and is not significant on employee performance with a hypothesis test calculation of t of 0.598 < 0.05 and a t value of 529 > t table 1.990. (4) calculating the F hypothesis with a significance value of 0.000 < 0.05 and an F value of 7,560 > F table 2.72, this shows that performance allowances (X1), organizational motivation (X2), and organizational culture (X3) simultaneously have a positive effect and significant to employee performance (Y).